Peran Kapabilitas SDM dalam Memoderasi Pengaruh Transformasi Digital terhadap Kinerja Keuangan Perbankan di Indonesia - Deasy Wulaningsih; Oktavia Oktavia (KOLONI, 2026)
The purpose of this research is to examine how digital transformation has affected the bottom lines of Indonesian banks, controlling for the moderating effect of digital HR capacity. Banks are being forced to abandon their physical business models in favour of an integrated digital ecosystem due to the acceleration of digitalisation in the aftermath of the pandemic. For this study, we used a quantitative methodology based on purposive selection to sift through the annual reports of traditional commercial banks trading on the IDX in Indonesia from 2022 to 2024. With the use of purposive sampling, 114 observations were obtained from 38 different banks. The analytical approach that was used to examine the moderating influence of HR capacity was panel data regression using a Fixed Effects Model (FEM) and Moderated Regression Analysis (MRA). The data was analysed using Moderated Regression Analysis (MRA) and Panel Data Regression. The results of the study show that return on investment (ROI) has not changed drastically due to digital investments. This shows that it takes some time for digital investments to pay off financially. On the other hand, OFFICE dramatically boosts ROA, suggesting that physical networks are remain valuable distribution assets that help banks turn a profit when they use a hybrid banking strategy. There is no evidence that HR capacity moderates the impact of INVESTMENT or OFFICE on ROA, according to the findings of the moderation test.According to this research, in order for banking digital transformation strategies to reap the full benefits of digital transformation in the long run, it is not enough to just invest in technology; strategies should also prioritise strengthening HR digital competencies and optimising the integration of digital and physical services.